Contesting community development: grounding definitions in practice contexts. Issue 3 (3rd April 2021) - Carlon, Colleen
ABSTRACT: Community development has many meanings. The strength of this conceptual openness is that it creates space for communities and their knowledges, values and interests. Its weakness is that, without general agreement on the nature of community development, the concept is applied inconsistently and becomes a "buzzword" which is high on application, yet low on meaning. This paper presents an analysis of community development as an essentially contested concept, highlighting descriptive and normative aspects of meanings and the role of context. It concludes with a range of actions that may assist in working through tensions between general definitions and conceptual openness.